Effects of peroxisome proliferator activated receptor gamma (PPAR gamma) agonist on fasting model applied neuron cultures - Pinarbasi, Arzu; Pak, Meltem; Kolay, Murat; Oz Arslan, Devrim; Aksungar, Fehime Benli (WALTER DE GRUYTER GMBH, 2022)
Objectives: Peroxisome proliferator activated receptor gamma (PPAR gamma) agonists used for the treatment of Diabetes Mellitus (DM), has important roles on the regulation of metabolism including ketogenesis in fasting and low glucose states. Recently PPAR gamma was proven to have antioxidant and anti-inflammatory effects on neuronal cells. Methods: In the present study, effects of pioglitazone (PPAR gamma agonist) on cell survival, energy metabolism and mitochondrial functions were investigated in glucose deprived fasting model applied SH-SY5Y (ATCC/CRL 2266) cell lines. Before and after pioglitazone treatment

energy metabolites (glucose, lactate, ketone (beta OHB), lactate dehydrogenase activity), mitochondrial citrate synthase activity and cell viability were investigated. Results and Conclusions: PPAR gamma agonist addition to glucose deprived, ketone added neurons provided positive improvements in energy metabolites (p<0.01), mitochondrial functions (p<0.001) and survival rates (p<0.01). Changes in mitochondrial citrate synthase activity, lactate and LDH levels of neuronal cells treated with PPAR gamma agonist have not been previously shown. Our results suggest, pioglitazone as an effective alternative for the treatment of neurodegenerative diseases especially with the presence of ketone bodies. By clarifying the mechanisms of PPAR gamma agonists, a great contribution will be made to the treatment of neurodegenerative diseases.
Keywords: fasting; ketone bodies; neuron cultures; pioglitazone; PPAR gamma